The Ritual Tradition of Esoteric Scientific Practices in Islamic Boarding Schools: A Study of Khizib Kubro Ismul Haq’s Practical Book - Faizin; Juniawan, Hendro Kartika; Witro, Doli; Muna, Moh. Nailul; Sidqi, Imaro (Tribakti: Jurnal Pemikiran Keislaman, 2025)
This paper examines the ritual tradition of esoteric scientific practices in Islamic boarding schools (pesantren), with a focus on the practical teachings outlined in the Kitab Amalan Khizib Kubro Ismul Haq. The study employs a qualitative research approach, utilizing library research methods. The primary data source is the Kitab Amalan Khizib Kubro Ismul Haq, along with supporting literature such as books, academic articles, and journals relevant to the research topic. Data collection is carried out through documentation, and content analysis is used for data analysis, incorporating techniques of data condensation, presentation, and conclusion drawing. The research findings reveal three main points. First, Islamic boarding schools (pesantren) are key institutions in preserving and developing Islamic traditions, including esoteric scientific practices. Second, esoteric practices are often misunderstood or negatively stigmatized due to a lack of comprehensive understanding, where the outward forms of the practices are emphasized over their deeper meanings. Third, the esoteric practices within pesantren share common ground with Sufism, as both emphasize inner spiritual transformation and the unveiling of hidden truths, with the ultimate aim of attracting benefits and avoiding harm for the practitioner. This paper aims to offer a fresh perspective on the esoteric ritual traditions in Islamic boarding schools and contribute to a deeper understanding of their role in Islamic spiritual practices.